Important Aspects of Post-Prandial Antidiabetic Drug, Acarbose - Kumar Singla, Rajeev; Singh, Radha; Kumar Dubey, Ashok (Current Topics in Medicinal Chemistry, 2016)
Acarbose, a well known and efficacious α-amylase and α-glucosidase inhibitor, is a postprandial acting antidiabetic drug. DNS-based α-amylase inhibitory assays showed that use of acarbose at concentrations above 125 μg/ml resulted in release of reducing sugar in the reaction, an unexpected observation. Objective of the present study was to design experimental strategies to address this unusual finding. Acarbose was found to be susceptible to thermo-lysis. Further, besides being an inhibitor, it could also be hydrolyzed by porcine pancreatic α-amylase, but had weaker affinity for α - amylase compared to starch. GRIP docking was done for the mechanistic analysis of the active site in the enzyme for substrate, inhibitor and, inhibitor’s metabolite (K2). Interaction between acarbose and α-amylase involved significant hydrogen binding compared to that of starch, producing a stronger enzyme-inhibitor complex. Further, docking analysis led us to predict the site on α-amylase where the inhibitor (acarbose) bound more tightly, which possibly affected the binding and hydrolysis of starch exerting its effective anti-diabetic function.
Keywords: α-Amylase inhibitor